Consumer Ethnocentrism, Market Mavenism and Social Network Analysis. Issue 3 (August 2018) - Cheah, Isaac; Shimul, Anwar Sadat
This study investigates the tendency of consumer ethnocentrism, the role of market mavenism and interactions between these two constructs within a social structure. A total of 215 responses were collected online using the snowballing technique. This study finds that younger consumers are less ethnocentric but demonstrate more mavenism than their counterparts. The social network analysis shows that within the 2-clique, the market mavens outnumbered the non-mavens. This paper provides a holistic view by incorporating the relationship among three concepts with six-degrees-of-separation theory, adding new insights into the constructs which was not previously addressed within the literature.